2017
DOI: 10.1177/2158244017722582
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Multiple Intelligences and Their Classroom Practice

Abstract: This study sought to investigate whether there are differences among EFL instructors of various intelligence types in terms of the types of activities that they implement in their classes. It also sought to investigate teachers' perceptions about the theory of multiple intelligences. To this end, 30 male and female EFL instructors teaching the same textbook with the same method of teaching participated in the present study. To gather the data, three successive sessions of each class were observed and the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
0
16
0
2
Order By: Relevance
“…On the other hand, we must consider that possibly the reason why students have little difference in the classifications of MI is that the teachers do not motivate their students to exercise it. There are certain studies where it has been found that the application of MI during class by teachers helps to improve the academic development of students (Dolati and Tahriri, 2017;Ghamrawi, 2014;Yaumi et al, 2018). In further research, this could be a better way to analyze MI by considering to study both the teacher and the students, not just one or the other.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we must consider that possibly the reason why students have little difference in the classifications of MI is that the teachers do not motivate their students to exercise it. There are certain studies where it has been found that the application of MI during class by teachers helps to improve the academic development of students (Dolati and Tahriri, 2017;Ghamrawi, 2014;Yaumi et al, 2018). In further research, this could be a better way to analyze MI by considering to study both the teacher and the students, not just one or the other.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, teachers need training on how to infuse MI in the curriculum framework to create authentic learning experiences that increase student performance (Johnson, 2007). Teachers' multiple intelligences and their classroom practices showed dominance in logical-mathematical intelligence in line with the activities they used (Dolati & Tahriri, 2017). If this is true, then, how can the potential for holistic development be formed when teachers set the limitations of the students' learning?…”
Section: Ctl's Theoretical Anchormentioning
confidence: 99%
“…Educación y TErriTorio iSSn:2256-3986 -imprESa iSSn: 2256-3431 ElEcTrónica Por lo tanto, una gran variedad de estudiosos de la teoría de Gardner (Gunst, 2004;Dolati y Tahriri, 2017;Ghamrawi, 2014;Serin, Serin, Yavuz y Muhammedzade, 2009;Ramírez, 2014) concuerdan con que hay una relación estrecha entre el estilo de enseñanza de los docentes y sus propias inteligencias predominantes, además de admitir la importancia de experimentar y estudiar dicha relación. Igualmente, es el mismo Gardner (1995), en su narrativa de "La teoría en la práctica", quien promueve la importancia del estudio y la revisión de su teoría al interior de la escuela y el salón de clases: "Dentro del área de la educación, actualmente muchos proyectos están examinando las aplicaciones de la teoría.…”
Section: La Inteligencia Del Docente Y La Influencia En Su Quehacerunclassified